LITHOPHYLLUM IPPOLITOI. A NEW SPECIES OF CORALLINE ALGAE FROM TERTIARY PIEDMONT BASIN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
A new species of the genus Lithophyllum (Lithophyllum ippolitoi) was discovered in the Oligocene section of Toleto (Molare Formation, Tertiary Piedmont Basin). The holotype overgrows a coral colony, and is characterised by morphological features and dimensions of cells that are clearly different from those of the other recorded species of Lithophyllum.
Keywords: Systematic palaeobotany; Corallinaceae; Lithophyllum; Oligocene; Tertiary Piedmont Basin.